Tasyaddud Abu Hatim Al-Raziy: Analisis Terhadap Perawi-Perawi Yang Dinilai Dengan Frasa “Laysa Bi Al-Qawiy” Dan “Laysa Biqawiy” - Jamilin, A. K. (Universiti Sains Islam Malaysia, 2024)
Abu Hatim Muhammad ibn Idris al-Raziy (277h) is a leading figure in the science of hadith among the first generation (mutaqaddimun) especially in the al-Jarh and al-Ta'dil discipline. However he was known as stern critic (mutasyaddid). But is the hypothesis true and supported by the valid evidence or strong arguement? Yet Abu Hatim made a lot of assessment and criticism on the narrators via different words and ways. The interpretation of his criticism sometime is ambiguous, and sometimes supplemented by a clear statement and proof. This ambiguity usually happened in his assessment because of the complexity of the utterance-words, multiple use of the structure, inconsistencies and sometimes because of the existence of contradictions. This matter may lead to confusion and misunderstanding among researchers of narrators or hadith. One of the utterances were: " Laysa bilqawiy" and "laysa biqawiy" meaning: Not strong, which denies the credibility of a narrator or denies it totally. However, based on preliminary observations of the author on the application of Abu Hatim when interacting with the phrase, he was seen as literally defying its use. This study aims to reveal in detail the truth about how strict Abu Hatim when he criticizing the narrators compared with other evaluators of narrators. The result is very important to understand part of the methodology of Abu Hatim and his utterance-words, which certainly have an impact on the assessment of hadith narrators, and at the same time the assessment of hadith which is the ultimate goals of al-Jarh and al-Ta'dil.